An Experimental Of 3D Gantry Crane System In Motion Control By PID And PD Controller Via PFPSO Optimization - Rozaimi, Ghazali (Universiti Teknikal Malaysia Melaka, 2016)
Gantry crane system is widely used for material transportation.In this system,uncontrolled oscillation always be found during the moving process.This problem may extend the carrying time and causes safety problem.This paper presents a method for controlling a Gantry Crane System based on Proportional-Integral-Derivative (PID)controller strategy.A combination of the Priority Fitness Scheme and Particle Swarm Optimization (PFPSO) is used to optimize five parameters of PID and PD controller (KP,KI, KD,KPs and KDs).The proposed method is examined in an experimental platform of 3D INTECO gantry crane system.Then the performance is compared with two other tuning methods which are Zeigler-Nichols (ZN) and Standard Particle Swarm Optimization (PSO).The performances of the system are assessed in terms of trolley position and payload oscillation.The results shown that the optimal parameters obtain from the PFPSO is the smallest and the trolley was able to reach at the desired position without creating an overshoot with low payload oscillation compared to ZN and PSO.